Catálise Enzimática na Síntese do Biodiesel de Mamona - Rios, Edilane de Sousa Gomes (2013)
The present study aimed to develop a method of obtaining biodiesel by methyl route, from castor oil using commercial enzymes and / or whole cells as biocatalysts through transesterification reactions. In developing this research were tested seven varieties of commercial enzymes and enzymatic some sources of plant (latex species Ficus benjamina, Manihot glaziovii Muell. Arg., Calotropis procera, Jatropha curcas L., Ficus pumila, Euphorbia tirucalli L. and seeds Lens culinaris). The chemical composition of castor oil was determined by gas chromatography-mass spectroscopy (GC-MS). The results showed the presence of fatty acids, palmitic, linoleic, oleic, stearic and ricinoleic identified and quantified in the form of their methyl esters. Almost 95% of the oil was composed of ricinoleic acid acid (12-hydroxy-9-octadecenoic). The enzymatic sources of plant origin were tested for hydrolytic activity to assess their potential as biocatalysts. From the results, two samples were selected to proceed with the experiments of biodiesel synthesis. The analysis of the biodiesel samples obtained by enzymatic synthesis was performed by GC-MS. The chromatographic method validation to analysis of castor bean biodiesel was done using solutions of previously synthesized methyl esters. Five calibration curves were obtained using the internal standard method for quantitation of each ester. Among the sources used in the enzymatic synthesis of biodiesel showed the best result was a commercial enzyme Novozym 435 forming 55.33% of biodiesel in the initial tests. Tests were conducted to optimize the following reaction parameters: pH, co-solvent ratio alcohol: oil, the amount of solvent to enzyme and recovering the enzyme. Keywords: Enzymes. Biodiesel. Transesterification. Castor Oil.